Belas Kasih Sebagai Spiritualitas Kemuridan Tuhan dan Kesiapsediaan Melayani Korban Bencana - Alfons Seran; Mawarni Gea; Fendi Aguswanto (Jurnal Magistra, 2024)
This research aims to discuss compassion as the spirituality of discipleship of God and readiness to serve disaster victims. In this modern world, humans live with sophisticated technology and communication tools, as well as internet access which is increasingly easy for anyone to do. Humans have contributed many things based on their knowledge and skills obtained from the development and progress of the times, but sometimes humans actually act arrogant, selfish, indifferent and jealous of other people's happiness. This fact shows that humans are experiencing a crisis in all aspects of life and are no longer merciful. This research uses qualitative methods with library research to collect reference materials in the form of books, Church documents and articles related to the title of this thesis. Many people think that compassion is only for those who need it. Even though compassion is more than sentimental attitudes and feelings. For this reason, the aim of writing this thesis is to offer the meaning and significance of compassion in human life. Compassion is an attitude of deeply feeling the suffering of others, namely sympathy, empathy, pity, care, generosity, simplicity of heart, humility and building a culture of compassion. The principle of mercy is to love God and fellow human beings as oneself.